KEPUTUSAN PEMBELIAN PADA GENERASI Z DITINJAU DARI ENDORSEMENT - Sunandie Eko Ginanjar; Desti Shalsabila; Riri Noviawati; Ridwan Faturohman (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
Influencer endorsements on TikTok are currently growing rapidly due to the large number of endorsers from various social media platforms, including TikTok and Instagram, as well as other social media platforms. Endorsements by influencers on TikTok are considered to have greater benefits compared to endorsements through other platforms. One of the stages of consumer behavior is the purchase decision, which underlies consumers to make purchase decisions so that it is known that social media influencers have a role in purchasing decisions in generation Z. The purpose of our research is to find out how much generation Z makes purchasing decisions in terms of endorsement influence. Here, we concentrate on the factors of trust, brand image, satisfaction, and content. This research was conducted using a qualitative approach.